Health Education and Mental Support Pre-Circumcision for Elementary School of Muhammadiyah Students - Tutur Kardiatun; Dinar Wulan Puspita; Tri Wahyuni; Indri Erwhani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The development of circumcision methods today has also developed rapidly, including conventional and modern methods. Circumcision requires preparation not only in terms of physical maturity but also psychological maturity. Mental problems felt by pre-circumcision children are fear of pain or anxiety about the circumcision process. Lack of information is a need for children for pre-circumcision mental preparation. The subjects of this activity were 69 students of Elementary School of Muhammadiyah 1, 2, and 3 Pontianak. Activities carried out on 21 February, 22 February, and third March 2023. This activity showed that the elementary school students were enthusiastic and active during the education provided. In addition to pre-circumcision health education, mental support for students aims to have mental readiness when circumcision time. At each venue, 60% of students were able to mention the purpose of circumcision, 70% of students were able to repeat deep breath relaxation techniques to reduce anxiety, and 78% of students stated that they were ready to be circumcised.Keywords: Circumcision, Health Education, Mental Support, Elementary Students.